Evil Feminine and Untamed Nerves: Sensationalism in J. Sheridan Le Fanu’s The Rose and the Key - Rossi, Stefano (Linguæ & - Journal of Modern Languages and Cultures, 2023)
Starting with a cultural-historical framing of late-Victorian sensation fiction and focusing on deranged and rebellious women that populate sensation narratives, this article explores the figure of J. Sheridan Le Fanu and his artistic closeness to late-Victorian sensationalism. Having as mainstay Le Fanu’s familiarity with late-nineteenth-century psychiatry, this paper pivots around the sensational that permeates Le Fanu’s The Rose and the Key, a work that never experienced the fame, for instance, of Uncle Silas or Carmilla. Paying attention to the stormy relationship between Maud and Barbara – daughter and mother, – and to the countless secrets guarded by the latter, in this article I look at The Rose and the Key as a denunciation of a highly corruptible psychiatric system, much oriented towards repression, especially in the case of women.